Going Deep: Service-Learning and Human Rights Education - Wolf, Christine A (Journal for the study of peace and conflict, 2012)
The concept of human rights for many North-American college students is associated with the 'other.' Those in need of human rights are perceived as nameless people living in the far corners of the globe. When I ask my students next semester who suffers from a lack of human rights, most will produce responses such as Africans or refugees. Some may include LGBT communities or children, but most responses will be vague and generic. Traditional-aged students generally don't feel a personal connection to the 'others' who are suffering or even recognize those 'others' in their midst, let alone some sense of responsibility around this concept. Unless human rights education ignites a sense of personal, hometown identification in the minds of students, as educators we lose long-term transformative possibilities. For what I term 'deep human rights learning' to occur, or an embodiment of the concept rather than merely an intellectual grasp, a creative synergy of diverse experiences best transforms both the individual and the class. In order to meet each student where they are in their perceptions and understanding of human rights, teachers need multiple ways to convey the subject. Learning about human rights requires a personal identification with otherness in order to be sustainable over time. How then do educators do better at creating a grounded solidarity, within and outside the classroom, fostering a shift from human rights being a mere subject to instead becoming a recognizable issue not separate from, but part of each student's personal experience? Adapted from the source document.